Preparation method of temperature response type composite hydrogel
By using temperature-responsive composite hydrogels prepared with carboxymethylcellulose and isopropyl acrylamide, the performance failure and structural instability caused by phase separation and volume shrinkage above LCST is solved, and a smart glass window application with high dimensional stability and rapid response is achieved.
Patent Information
- Application Number
- CN202411610649.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The existing temperature-sensitive hydrogels above LCST have failed performance and unstable structure due to phase separation and volume shrinkage, making them difficult to be suitable for smart glass windows.
Carboxymethylcellulose and isopropylacrylamide are used as the main materials to prepare a temperature-responsive composite hydrogel by initiating a polymerization reaction, which has a phase change temperature of 29~32°C and rapidly changes transparency when the temperature changes.
The prepared composite hydrogel has the characteristics of high dimensional stability and rapid response to temperature changes. It is suitable for smart glass windows. It can quickly become opaque when it heats up to scatter sunlight, meeting building energy-saving needs.
Smart Images

Figure CN119613640A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of intelligent polymer materials, and specifically relates to a method for preparing a thermosensitive hydrogel, and in particular to a method for synthesizing a thermosensitive composite hydrogel using polyisopropylacrylamide as a thermosensitive polymer and a transparent water-soluble polymer as a hydrogel main material. Background Art
[0002] At present, global building energy consumption accounts for about 30%-40% of all energy consumption, of which cooling and heating account for more than half. In the current context of "carbon neutrality", green and energy-saving buildings have become a necessity for environmental protection and market development. As the main channel for heat exchange between buildings and the outside world, windows are of great significance in green buildings. Windows are the main lighting components of buildings. In summer, sunlight entering the room through glass will cause indoor overheating; in order to block the sunlight, blinds, curtains, etc. block the sunlight while also reducing the indoor illumination. New dynamic glass systems (smart windows) based on smart materials have great potential for reducing the overall energy demand of the construction industry. Smart windows can adjust light transmittance to achieve optimal control of the light and heat environment of the room, and save energy consumption for building heating, cooling and ventilation by controlling solar energy transmission.
[0003] The adjustment principle of smart windows is mainly to adjust the transmittance of light entering the glass according to different environments through the effect of the color-changing materials in the windows, so as to achieve the purpose of regulating the indoor environment and temperature. According to the different color-changing mechanisms, smart windows can be roughly divided into the following three categories: electrochromic smart windows, photochromic smart windows, and thermochromic smart windows. Qin et al. [1] used a one-pot method to add WO 3 Nanoparticles are used to prepare a new type of photochromic nanocomposite organic hydrogel (NC OGHs). Photochromic NC OGHs have excellent properties, including high transparency, excellent mechanical properties, resistance to low temperatures and UV shielding. However, due to the high production cost and complicated processing procedures, it is not suitable for commercial applications of large-area color-changing smart glass; electrochromic smart windows can meet user needs through active adjustment, but their disadvantage is that DC power supply is required to stimulate the response of such smart windows, and the transparent film prepared based on the liquid crystal display mechanism has high production costs. Compared with electrochromic smart windows, which require external continuous voltage to maintain the color-changing state of the electrochromic device, thermochromic smart windows only need to change the temperature in the external environment to switch between transparent and opaque states. At the same time, the preparation process of thermochromic smart windows is simple and the structure is simple.
[0004] Among the many thermochromic materials, isopropyl acrylamide is one of the most widely studied materials. The lower critical solution temperature (LCST) of poly (N-isopropyl acrylamide) (PNIPAM) is about 32°C. Due to its unique temperature sensitivity, PNIPAM has been widely studied and applied in many fields, such as drug controlled release, biosensors, tissue engineering, and temperature regulation. But when applied to buildings, we need to consider other indicators of smart windows, such as a comfortable phase transition temperature close to human body temperature, visible light transmittance, stability, and suitability for large-scale production. Considering these performance requirements, PNIPAM gels and microparticles are the best candidates for smart windows. Thermosensitive hydrogels can sense subtle physical and chemical changes in external environmental stimuli such as pH, temperature, electric field, ionic strength, etc. and produce responsive behaviors. The reason why thermosensitive gels can undergo phase changes (swelling and shrinkage) in response to temperature changes is that this type of gel has a certain proportion of hydrophobic and hydrophilic groups. Changes in temperature can affect the hydrophobic effect of these groups and the hydrogen bonding effect between macromolecular chains, thereby changing the gel structure and causing a volume phase change. The biggest feature of thermosensitive hydrogels is that they have a minimum critical phase transition temperature (LCST).
[0005] As early as 2019, the grafted P (DMAEMAM-NIPAM) copolymer synthesized in aqueous solution had good fluidity and was easy to inject into architectural laminated glass, but people gradually discovered that this copolymer was prone to leakage and water was easy to evaporate. In order to solve this problem, the copolymer hydrogel was obtained by in situ copolymerization, and the PNIPAM gel was sealed in the double-layer glass. However, above the LCST, due to obvious phase separation (separation of cross-linked copolymer and water) and volume shrinkage, the cross-linked PNIPAM network prepared by this method is easy to precipitate from the hydrogel, which can easily lead to failure of the hydrogel performance and structural instability, limiting its precise use in confined spaces.
[0006] The main problems currently exist are: ① Liquid thermosensitive materials have the risk of leakage; ② In-situ copolymerized hydrogels shrink due to phase separation at LCST, making it difficult to make smart glass windows. Based on the above background, the present invention proposes a dimensionally stable fast thermosensitive response composite hydrogel and a preparation method thereof, which has important practical significance and application value. Summary of the invention
[0007] The purpose of the present invention is to solve the problems involved in the above background technology, and provide a method for preparing a thermosensitive responsive composite hydrogel. The material prepared by this method has high dimensional stability and can quickly respond to temperature to change its own transparency. At the same time, the preparation method has a short synthesis route and a simple process.
[0008] Specifically, the present invention adopts the following technical scheme: a method for preparing a thermosensitive responsive polycomposite hydrogel, comprising the following steps: A method for preparing a temperature-responsive composite hydrogel comprises the following steps: (1) mixing the carboxymethyl cellulose solution and the isopropyl acrylamide monomer at room temperature to obtain a mixture a; (2) adding ammonium persulfate initiator to mixture a and heating to initiate polymerization to obtain mixture b; (3) dissolving monomer acrylamide, N,N-methylenebisacrylamide crosslinking agent, and ammonium persulfate initiator in mixture b to obtain mixture c; (4) The mixture c is polymerized by heating to obtain a composite thermosensitive hydrogel.
[0009] In the step (1), a carboxymethyl cellulose solution having a mass concentration of 0.5% to 2% and an isopropyl acrylamide monomer accounting for 0.5% to 10% of the total mass of the solution are uniformly mixed at room temperature to obtain a mixture a; 0.5% of ammonium persulfate accounting for the monomer amount is dissolved in mixture a and the temperature is raised to 5-85° C. to initiate a polymerization reaction. The reaction time is 4-8 hours to obtain mixture b.
[0010] In step (3), the amount of acrylamide added is 2-20% of the total mass of the mixture c; The mass ratio of acrylamide, N,N-methylenebisacrylamide crosslinking agent, and initiator is 100: 0.5~1: 0.1~0.5.
[0011] In the step (4), acrylamide monomer, crosslinking agent and initiator are dissolved in mixture b at a temperature lower than the phase transition temperature of the aqueous solution of polyisopropylacrylamide (i.e., mixture b) to obtain mixture c; the phase transition temperature of the aqueous solution of polyisopropylacrylamide is 32°C.
[0012] In step (4), the polymerization reaction temperature is 5-85° C. and the reaction time is 4-8 hours.
[0013] At the phase transition temperature of polyisopropylacrylamide aqueous solution of 32°C, 5~31°C, acrylamide monomer, crosslinking agent and initiator are dissolved in mixture b to obtain mixture c, and injected between parallel glass plates. The hydrogel obtained by low-temperature polymerization has shrinkage.
[0014] At the phase transition temperature of polyisopropylacrylamide aqueous solution of 32°C, 33~85°C, acrylamide monomer, crosslinking agent and initiator are dissolved in mixture b to obtain mixture c, and injected between parallel glass plates. The hydrogel obtained by high-temperature polymerization has shrinkage.
[0015] A temperature-responsive composite hydrogel is prepared by the method, wherein the phase transition temperature of the composite hydrogel is 29-32° C. When the temperature is raised to above the phase transition temperature, a transition from transparent to opaque occurs, and when the temperature is lowered to below the phase transition temperature, a transition from opaque to transparent occurs.
[0016] The transition time is less than 5 s, preferably less than 3 s, and more preferably less than 1 s.
[0017] Another technical solution of the present invention is to provide a composite hydrogel for smart glass windows, including the temperature-responsive composite hydrogel prepared by the method described.
[0018] The composite hydrogel for smart glass windows is prepared by injecting the above-mentioned mixture C into 0.5-20 mm parallel glass plates and sealing them, and heating to initiate polymerization to obtain a composite thermosensitive hydrogel formed in the parallel glass plates.
[0019] The composite thermosensitive hydrogel formed in the parallel glass plates undergoes a transition from transparent to opaque when the temperature rises to the phase transition temperature, and undergoes a transition from glass opaque to transparent when the temperature drops below the phase transition temperature. The phase transition temperature is 29-32°C.
[0020] The transition time is less than 5 s, preferably less than 3 s, and more preferably less than 1 s.
[0021] The prepared fast temperature-sensitive response polyacrylamide composite hydrogel has phase change shrinkage properties and is suitable for applications such as smart sensors.
[0022] A temperature-responsive composite hydrogel, wherein the monomer acrylamide in the gel matrix material of the temperature-responsive composite hydrogel can also be replaced by acrylic acid, sodium acrylate, hydroxyethyl acrylate, N-vinyl pyrrolidone, and the water-soluble polymer is any one of polyacrylic acid, polyvinyl alcohol, and polyethylene glycol. The monomer acrylamide is included, and the corresponding gel matrix material of the temperature-responsive composite hydrogel includes any one of polyacrylamide PAM, polyacrylic acid PAA, sodium polyacrylate PAANa, polyhydroxyethyl acrylate PHEA, polyvinyl pyrrolidone PVP, polyvinyl alcohol PVA, and polyethylene glycol PEG.
[0023] Compared with the prior art, the present invention has the following beneficial effects: (1) The phase transition temperature of the CMC-PNIPAM / PAM composite hydrogel prepared by the present invention is 29-32°C. The composite hydrogel can be used as smart glass. The ambient temperature can change the dissolution state of the thermosensitive polymer in the smart composite hydrogel. When the temperature exceeds the critical dissolution temperature of the thermosensitive polymer, the thermosensitive polymer in the hydrogel changes from a dissolved state to an insoluble state, and the appearance of the hydrogel changes from a colorless and transparent state to a white and opaque state, scattering sunlight and meeting the energy-saving requirements of buildings.
[0024] (2) The preparation method does not involve complicated equipment, the raw materials are cheap, and the process is simple and easy; (3) Two types of temperature-responsive hydrogels can be obtained through this process, namely, two types of hydrogels that cannot shrink after phase change and whose size and shape remain stable, and two types of hydrogels that can shrink. They respond quickly to temperature changes, and the gel transparency changes significantly. This is the originality of this process: when the CMC-PNIPAM aqueous solution is above its phase change temperature, the thermosensitive polymer PNIPAM precipitates from the water (self-assembles into tiny particles), but with the protection of the CMC polymer, the PNIPAM particles will not precipitate and separate from the water; then, acrylamide (AM), crosslinking agent, initiator, etc. are added to the CMC-PNIPAM aqueous solution above the phase change temperature of the thermosensitive polymer PNIPAM, mixed evenly, and polymerized to obtain a composite hydrogel. The hydrogel does not shrink before and after the phase change, and is suitable for smart glass window applications. However, as long as the process conditions are changed, acrylamide (AM), crosslinking agent, initiator, etc. are added to the CMC-PNIPAM aqueous solution below the phase change temperature of the thermosensitive polymer PNIPAM, mixed evenly, and polymerized to obtain a shrinkable composite hydrogel, that is, the hydrogel shrinks before and after the phase change, and is suitable for use in materials such as smart sensors.
[0025] (4) During the heating process, the hydrogel rapidly undergoes a reversible change (<5 s) from transparent to opaque, which makes it have broad application prospects in temperature-sensitive detection / sensing devices, smart optical devices, flexible smart devices, and smart optical components. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The states of hydrogels synthesized from 6 substrates at LCST. The hydrogel substrates are: PAM, PVA, PAA, PAANa, PEG, and PVP.
[0027] Figure 2 The states of the composite hydrogel of the present invention at low temperature (25°C, left) and high temperature (35°C, right) (hydrogel substrate: PAM, sample 1).
[0028] Figure 3 Window viewing angles of the thermoresponsive composite hydrogel material of the present invention below LCST (left) and above LCST (right).
[0029] Figure 4 Schematic diagram of the preparation principle of thermosensitive hydrogel materials.
[0030] Figure 5 Flow chart of the preparation of thermosensitive hydrogel materials. Figure 6 Schematic diagram of the color-changing mechanism of thermosensitive hydrogel material as smart glass window.
[0031] Figure 7 Comparison of the phase separation states of shrinkable thermosensitive hydrogel material (left) and non-shrinkable thermosensitive hydrogel material (right) after phase change. DETAILED DESCRIPTION
[0032] Example 1 This embodiment provides a method for preparing a non-shrinkage temperature-responsive composite hydrogel, comprising the following steps: (1) Dissolve 1 g of carboxymethyl cellulose in 99 g of deionized water, heat and stir until the carboxymethyl cellulose is completely dissolved and the solution is transparent, to obtain a carboxymethyl cellulose solution with a mass fraction of 1%.
[0033] (2) 94 g of carboxymethyl cellulose solution and 6 g of isopropyl acrylamide were mixed and dissolved uniformly, and 0.03 g of APS was added to initiate polymerization at 80° C. for 5 h to obtain a mixture 2.
[0034] (3) Take 90 g of the mixture 2 obtained in (2) and mix it with 10 g acrylamide and dissolve it evenly. Heat it to 55 °C, add 0.1 g BIS and 0.05 g APS, mix evenly, and initiate polymerization at 55 °C for 3 h. Then heat it to 80 °C and polymerize it for 3 h to obtain a thermosensitive hydrogel, which is recorded as sample 1.
[0035] Example 2 This example provides a method for preparing a non-shrinkage temperature-responsive composite hydrogel (Sample 2), which is similar to Example 1, except that the concentration of carboxymethyl cellulose is 0.5%. The preparation steps are as follows: 0.5 g of carboxymethyl cellulose was dissolved in 99.5 g of deionized water, and the mixture was heated and stirred until the carboxymethyl cellulose was completely dissolved and the solution was transparent, thereby obtaining a carboxymethyl cellulose solution with a mass fraction of 0.5%.
[0036] Example 3 This example provides a method for preparing a non-shrinkage temperature-responsive composite hydrogel (Sample 3), which is similar to Example 1, except that the concentration of carboxymethyl cellulose is 2%. The preparation steps are as follows: Dissolve 2 g of carboxymethyl cellulose in 98 g of deionized water, heat and stir until the carboxymethyl cellulose is completely dissolved and the solution is transparent, to obtain a carboxymethyl cellulose solution with a mass fraction of 2%.
[0037] Example 4 This example provides a method for preparing a non-shrinkage temperature-responsive composite hydrogel (Sample 4), which is similar to Example 1, except that the mass fraction of isopropyl acrylamide is 0.5%, and comprises the following steps: (1) Dissolve 1 g of carboxymethyl cellulose in 99 g of deionized water, heat and stir until the carboxymethyl cellulose is completely dissolved and the solution is transparent, to obtain a carboxymethyl cellulose solution with a mass fraction of 1%.
[0038] (2) 99.5 g of carboxymethyl cellulose solution and 0.5 g of isopropyl acrylamide were mixed and dissolved uniformly, and 0.0025 g of APS was added to initiate polymerization at 80° C. for 5 h to obtain a mixture 2.
[0039] (3) 90 g of the mixture 2 obtained in (2) was mixed with 10 g of acrylamide and dissolved uniformly, and the mixture was heated to 55°C. 0.1 g of BIS and 0.05 g of APS were added and mixed uniformly. The mixture was then polymerized at 55°C for 3 h, and then the mixture was heated to 80°C for 3 h.
[0040] Example 5 This example provides a method for preparing a non-shrinkage temperature-responsive composite hydrogel (Sample 5), which is similar to Example 1, except that the mass fraction of isopropyl acrylamide is 10%, and comprises the following steps: (1) Dissolve 1 g of carboxymethyl cellulose in 99 g of deionized water, heat and stir until the carboxymethyl cellulose is completely dissolved and the solution is transparent, to obtain a carboxymethyl cellulose solution with a mass fraction of 1%.
[0041] (2) 90 g of carboxymethyl cellulose solution and 10 g of isopropyl acrylamide were mixed and dissolved uniformly, and 0.05 g of APS was added to initiate polymerization at 80° C. for 5 h to obtain a mixture 2.
[0042] (3) 90 g of the mixture 2 obtained in (2) was mixed with 10 g of acrylamide and dissolved uniformly, and the mixture was heated to 55°C. 0.1 g of BIS and 0.05 g of APS were added and mixed uniformly. The mixture was then polymerized at 55°C for 3 h, and then the mixture was heated to 80°C for 3 h.
[0043] Example 6 This example provides a method for preparing a non-shrinkage temperature-responsive composite hydrogel (Sample 6), which is similar to Example 1, except that the mass fraction of acrylamide is 2%, and includes the following steps: (1) Dissolve 1 g of carboxymethyl cellulose in 99 g of deionized water, heat and stir until the carboxymethyl cellulose is completely dissolved and the solution is transparent, to obtain a carboxymethyl cellulose solution with a mass fraction of 1%.
[0044] (2) 94 g of carboxymethyl cellulose solution and 6 g of isopropyl acrylamide were mixed and dissolved uniformly, and 0.03 g of APS was added to initiate polymerization at 80° C. for 5 h to obtain a mixture 2.
[0045] (3) Take 98 g of the mixture 2 obtained in (2) and mix with 2 g of acrylamide and dissolve evenly, heat to 55°C, add 0.02 g of BIS and 0.01 g of APS, mix evenly, initiate polymerization at 55°C for 3 h, and then heat to 80°C for 3 h.
[0046] Example 7 This example provides a method for preparing a non-shrinkage temperature-responsive composite hydrogel (Sample 7), which is similar to Example 1, except that the mass fraction of acrylamide is 20%, and includes the following steps: (1) Dissolve 1 g of carboxymethyl cellulose in 99 g of deionized water, heat and stir until the carboxymethyl cellulose is completely dissolved and the solution is transparent, to obtain a carboxymethyl cellulose solution with a mass fraction of 1%.
[0047] (2) 94 g of carboxymethyl cellulose solution and 6 g of isopropyl acrylamide were mixed and dissolved uniformly, and 0.03 g of APS was added to initiate polymerization at 80° C. for 5 h to obtain a mixture 2.
[0048] (3) 80 g of the mixture 2 obtained in (2) was mixed with 20 g of acrylamide and dissolved uniformly, and the mixture was heated to 55°C. 0.2 g of BIS and 0.1 g of APS were added and mixed uniformly, and polymerization was initiated at 55°C for 3 h, and then the mixture was heated to 80°C for 3 h.
[0049] Example 8 This example provides a method for preparing a post-phase-change shrinkage temperature-responsive composite hydrogel (Sample 8), which is similar to Example 1, except that the initial polymerization temperature in step 3 is below the 32°C phase change temperature of polyisopropylacrylamide, and the synthesis steps are: (1) Dissolve 1 g of carboxymethyl cellulose in 99 g of deionized water, heat and stir until the carboxymethyl cellulose is completely dissolved and the solution is transparent, to obtain a carboxymethyl cellulose solution with a mass fraction of 1%.
[0050] (2) 94 g of carboxymethyl cellulose solution and 6 g of isopropyl acrylamide were mixed and dissolved uniformly, and 0.03 g of APS was added to initiate polymerization at 80° C. for 5 h to obtain a mixture 2.
[0051] (3) 90 g of the mixture 2 obtained in (2) was mixed with 10 g of acrylamide and dissolved uniformly, cooled to 20°C with 5°C cold water, 0.1 g of BIS and 0.05 g of APS were added and mixed uniformly, and polymerization was initiated at 25-30°C for 5 h, and then the temperature was raised to 80°C for polymerization for 3 h.
[0052] Example 9 In addition to acrylamide (AM), there are many other substrates commonly used to prepare gels. The monomers include acrylic acid (AA), sodium acrylate (AANa), hydroxyethyl acrylate (HEA), N-vinyl pyrrolidone (NVP), and the water-soluble polymers include polyacrylic acid (PAA), polyvinyl alcohol (PVA), and polyethylene glycol (PEG). In this example, polyacrylic acid (PAA), sodium polyacrylate (PAANa), polyhydroxyethyl acrylate (PHEA), and polyvinyl pyrrolidone (PVP) were selected as the coagulation substrates to prepare thermosensitive hydrogels.
[0053] When monomer polymerization is used to prepare the thermosensitive hydrogel, the synthesis steps are similar to those in Example 1, except that in step (3), the monomer AM is replaced by acrylic acid (AA), sodium acrylate (AANa), hydroxyethyl acrylate (HEA), and N-vinyl pyrrolidone (NVP) to prepare hydrogels based on PAA, PAANa, PHEA, and PVP, respectively. The corresponding hydrogels are recorded as sample 9, sample 10, sample 11, and sample 12.
[0054] Example 10 When the thermosensitive hydrogel is prepared using water-soluble polymers polyvinyl alcohol (PVA) and sodium polyacrylate (PAANa) as raw materials, the synthesis process of the thermosensitive polymer is similar to that of Example 1; in order to facilitate the uniform mixing of the water-soluble polymers PVA and PAANa with the mixture 2, the water-soluble polymers PVA and PAANa are first dissolved in deionized water into a 20% aqueous solution for standby use. At the same time, in order to make the mass fraction of CMC-PNIPAM in the hydrogel 6%, the mass fraction of CMC-PNIPAM synthesized in step 2 is increased to 12%. The specific synthesis steps are as follows: (1) Dissolve 1 g of carboxymethyl cellulose in 99 g of deionized water, heat and stir until the carboxymethyl cellulose is completely dissolved and the solution is transparent, to obtain a carboxymethyl cellulose solution with a mass fraction of 1%.
[0055] (2) 88 g of carboxymethyl cellulose solution and 12 g of isopropyl acrylamide were mixed and dissolved uniformly, and 0.06 g of APS was added to initiate polymerization at 80° C. for 5 h to obtain a mixture 2.
[0056] (3) For the water-soluble polymer PVAa, the synthesis process is as follows: weigh 50 g of mixture 2 and mix it evenly with 50 g of the prepared water-soluble polymer PVA (mass fraction of 20%), place it in a vacuum degassing machine to remove bubbles, then add 1 g of glutaraldehyde (50% aqueous solution), stir evenly to remove bubbles, and place it in a mold at 50°C for 8 h to cross-link the PVA, thereby obtaining a thermosensitive hydrogel, which is recorded as sample 13.
[0057] For the water-soluble polymer PAANa, the synthesis process is as follows: weigh 50g of mixture 2 and mix it evenly with 50g of the prepared water-soluble polymer PAANa (mass fraction of 20%), place it in a vacuum degassing machine to remove bubbles, and then add 1g of aziridine crosslinker (50% trifunctional aziridine crosslinker aqueous solution, trimethylolpropane-tri[3-(2-methylaziridinyl)] propionate), stir evenly, remove bubbles, and let it stand in a mold at 50°C for 8 h to crosslink PAANa, and then the thermosensitive hydrogel can be obtained, which is recorded as sample 14.
[0058] The above examples clearly and completely describe the technical solutions in the present invention. The described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The above are only preferred implementation modes of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and deformations can be made without departing from the technical principles of the present invention, and these improvements and deformations should also be regarded as the scope of protection of the present invention.
[0059]
[0060] like Figure 1 As shown in the figure, when the temperature is above the LCST, the composite hydrogel prepared by AM has the best performance (sample 1). PVA, PAA, and PAANa are uneven after color change; PEG and PVP do not change color completely and cannot play a complete shielding role. Therefore, AM is the most preferred choice as the substrate.
Claims
1. A method for preparing a temperature-responsive composite hydrogel, characterized in that: The following steps are involved: (1) mixing the carboxymethyl cellulose solution and the isopropyl acrylamide monomer at room temperature to obtain a mixture a; (2) adding ammonium persulfate initiator to mixture a and heating to initiate polymerization to obtain mixture b; (3) dissolving monomer acrylamide, N,N-methylenebisacrylamide crosslinking agent, and ammonium persulfate initiator in mixture b to obtain mixture c; (4) Injecting the mixture c into a mold to initiate polymerization to obtain a composite thermosensitive hydrogel.
2. The preparation method according to claim 1, characterized in that: A carboxymethyl cellulose solution with a mass concentration of 0.5% to 2% and an isopropyl acrylamide monomer with a mass concentration of 0.5% to 10% of the total mass of the solution are uniformly mixed at room temperature to obtain a mixture a; 0.1-0.5% of ammonium persulfate accounting for the monomer amount is dissolved in mixture a and the temperature is raised to 5-85° C. to initiate a polymerization reaction. The reaction time is 4-8 hours to obtain mixture b.
3. The preparation method according to claim 1, characterized in that: In step (3), the amount of acrylamide added is 2-20% of the total mass of the mixture c; The mass ratio of acrylamide, N,N-methylenebisacrylamide crosslinking agent, and initiator is 100: 0.5~1: 0.1~0.
5.
4. The preparation method according to claim 1, characterized in that: In step (4), the polymerization reaction temperature is 5-90° C. and the reaction time is 4-8 hours.
5. The preparation method according to claim 4, characterized in that: At the phase transition temperature of polyisopropylacrylamide aqueous solution of 32°C, 5~31°C, acrylamide monomer, crosslinking agent and initiator are dissolved in mixture b to obtain mixture c, and injected between parallel glass plates. The hydrogel obtained by low-temperature polymerization has shrinkage.
6. The preparation method according to claim 4, characterized in that: At the phase transition temperature of polyisopropylacrylamide aqueous solution of 32°C, 33~85°C, acrylamide monomer, crosslinking agent and initiator are dissolved in mixture b to obtain mixture c, and injected between parallel glass plates. The hydrogel obtained by high-temperature polymerization has shrinkage.
7. A temperature-responsive composite hydrogel, characterized in that: The composite hydrogel is prepared by the method according to any one of claims 1 to 5, wherein the phase transition temperature of the composite hydrogel is 29-32°C, and a transition from transparent to opaque occurs when the temperature is raised above the phase transition temperature, and a transition from opaque to transparent occurs when the temperature is lowered below the phase transition temperature.
8. A composite hydrogel for smart glass windows, characterized in that: The invention relates to a temperature-responsive composite hydrogel prepared by the method according to any one of claims 1 to 5.
9. The composite hydrogel for smart glass window according to claim 7, characterized in that: The mixture c was injected into parallel glass plates with a diameter of 0.5-20 mm and sealed, and the polymerization was initiated by heating to obtain a composite thermosensitive hydrogel formed in the parallel glass plates.
10. A temperature-responsive composite hydrogel, characterized in that: The monomer acrylamide in the gel matrix material of the temperature-responsive composite hydrogel can also be replaced by any one of acrylic acid, sodium acrylate, hydroxyethyl acrylate, N-vinyl pyrrolidone, polyacrylic acid, polyvinyl alcohol, and polyethylene glycol.
Citation Information
Patent Citations
Intelligent high water absorption and waterholding material and preparation method and application thereof in desertification control
CN101974192A
Thermo-sensitive fluorescent carbon nano composite material and preparation method thereof
CN103204972A
Super absorbent resin containing montmorillonite and preparation method thereof
CN109970917A
Thermochromic hydrogel type intelligent window as well as preparation method, product and application thereof
CN112279945A
Preparation method of interpenetrating network polymer hydrogel with temperature responsiveness
CN113667146A
Cited By
Temperature-pH double-response type hydrogel, preparation method and fire extinguishing agent thereof
CN120829544A
Temperature-pH dual-responsive hydrogel, preparation method and fire extinguishing agent thereof
CN120829544B
Whitening type temperature indicator based on polyvinyl acetal polymer
CN122149675A